2017
DOI: 10.21500/20112084.2760
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive stimulation in children at social risk: its transference to school performance

Abstract: Intervención cognitiva grupal destinada a fortalecer funciones ejecutivas en niños en riesgo socialCelina Korzeniowski 1 2 *, Mirta Susana Ison 1 2 and Hilda Difabio 3 AbstractThe present study set out to evaluate the effectiveness of a group cognitive intervention aimed at promoting executive functions in children at social risk. The quasi-experimental, pretest-posttest design included a control group. The sample was made up of 178 children (52% boys), aged 6-10. The children were evaluated by means of a batt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 37 publications
0
5
0
2
Order By: Relevance
“…Lezama et al (2019) Desarrollo e implementación de una propuesta didáctica para la promoción de la función ejecutiva "planificación y organización" en cursos de física de enseñanza media. Un estudio de caso realizado en Uruguay Korzeniowski et al (2017) Intervención cognitiva grupal dirigida al fortalecimiento de las funciones ejecutivas en niños en riesgo social. Mayoral et al (2015) Mejora de la capacidad de planificación cognitiva del alumnado de primer curso de Educación Secundaria Obligatoria Cardoso et al (2019) Programa para la estimulación neuropsicológica de la cognición en estudiantes: efectos de impacto, efectividad y transferencia en el desempeño cognitivo del estudiante.…”
Section: N Autor Títulounclassified
“…Lezama et al (2019) Desarrollo e implementación de una propuesta didáctica para la promoción de la función ejecutiva "planificación y organización" en cursos de física de enseñanza media. Un estudio de caso realizado en Uruguay Korzeniowski et al (2017) Intervención cognitiva grupal dirigida al fortalecimiento de las funciones ejecutivas en niños en riesgo social. Mayoral et al (2015) Mejora de la capacidad de planificación cognitiva del alumnado de primer curso de Educación Secundaria Obligatoria Cardoso et al (2019) Programa para la estimulación neuropsicológica de la cognición en estudiantes: efectos de impacto, efectividad y transferencia en el desempeño cognitivo del estudiante.…”
Section: N Autor Títulounclassified
“…According those frameworks, a set of evidencebased approaches and strategies for teachers to help children lowering stress and promote EFs during the COVID-19 pandemic, have been selected. Those strategies have been chosen from: peer-reviewed academic publications, books and web resources, published between 2010 and 2021: For lowering children sress: [8,26,89,[93][94][95][96][97][98][99] and for promoting children EFs [100][101][102][103][104][105][106][107][108]. As a result, a collection of techniques was created that can easily be embedded into the school curriculum, while also encouraging cooperation between teachers, and between teachers and families.…”
Section: Implications For School-based Interventions: Teacher's Strat...mentioning
confidence: 99%
“…For example, a large study from rural Pakistan showed that an intervention designed to increase cognitive stimulation in the home environment in the first two years of life led to higher executive function and verbal IQ later in development (Obradović et al, 2016). Studies have also shown that cognitive stimulation programs to be associated with increases in reading comprehension scores (Reina-Reina et al, 2023) as well as cognitive flexibility, planning, metacognition and inhibitory control (Korzeniowski et al, 2017). Although not the direct results of an intervention, findings from Early Head Start, a federally funded intervention program, found that cognitive stimulation in the home, rather than participation in the program, explained variation in children's vocabulary development (Chapin & Altenhofen, 2010).…”
Section: Interventions Targeting Cognitive Stimulationmentioning
confidence: 99%